Attentional bias for high-calorie food cues by the level of hunger and satiety in individuals with binge eating behaviors - Woo, Ji-Min; Lee, Gi-Eun; Lee, Jang-Han (Frontiers in Neuroscience, 2023)
The abnormal hyperreactivity to food cues in individuals with binge eating problems could be regulated by hedonic or reward-based system, overriding the homeostatic system. The aim of the present study was to investigate whether attentional bias for food cues is affected by the level of hunger, maintaining the normal homeostatic system in individuals with binge eating problem. A total of 116 female participants were recruited and divided into four groups: hungry-binge eating group (BE) (n=29), satiated BE (n=29), hungry-control (n=29), satiated control (n=29). While participants completed a free-viewing task on high or low-calorie food cues, visual attentional processes were recorded using an eye tracker. The results revealed that BE group showed longer initial fixation duration toward highcalorie food cues in both hunger and satiety condition in the early stage, whereas the control group showed longer initial fixation duration toward high-calorie food cues only in hunger conditions. Moreover, in the late stage, the BE group stared more at the high-calorie food cue, compared to control group regardless of hunger and satiety. The findings suggest that automatic attentional bias for food cues in individuals with binge eating problem occurred without purpose or awareness is not affected by the homeostatic system, while strategic attention is focused on high-calorie food. Therefore, the attentional processing of food cues in binge eating group is regulated by hedonic system rather than homeostatic system, leading to vulnerability to binge eating.